Nexus between Innovation and Ecological Impact: A Moderated Mediation Investigation through Structural Equation Modeling Approach - Sulehri, Fiaz Ahmad; Audi, Marc; Poulin, Marc; Ali, Amjad (International Journal of Energy Economics and Policy, 2024)
Controlling ecological deterioration is critical for the well-being of current and future generations, as it ensures a sustainable environment that promotes health, productivity, and the general quality of life. This study investigates the interplay between innovation, economic growth, and ecological impact across 18 countries, which collectively account for approximately 64% of global greenhouse gas emissions, using data from 2000 to 2022. Using the structural equation modeling approach, we investigate how the regulatory framework moderates and economic growth mediates these complex relationships. The empirical results reveal that innovation positively impacts economic growth, but this effect is statistically insignificant. Similarly, economic growth contributes significantly to environmental degradation. Moreover, the interaction between innovation and the regulatory framework leads to a decline in economic growth. Furthermore, innovation alone in a direct relationship, reduces ecological impact significantly but innovation and regulatory framework jointly increase ecological impact. Economic growth plays a significant role in mediating the relationship between the interaction term and ecological impact, but it does not significantly influence the relationship between innovation and ecological impact, according to empirical evidence. These insights are vital for policymakers to develop strategies that encourage sustainable growth and innovation.